Role of dietary intervention on sugar-sweetened beverages, fruit juices and milk consumption among obese children/adolescents - Valentina Rahelić; Eva Pavić; Suzana Rimac Brnčić; Ines Panjkota Krbavčić; Ivana Rumora Samarin (Mljekarstvo)
The increase in childhood obesity is one of the biggest public health problems of the 21st century. Among the contributing dietary factors is the high consumption of sugar-sweetened beverages (SSB) and sweetened fruit juices (SFJ). On the other hand, regular consumption of milk and dairy products has decreased in many countries over the years, although research has shown an inverse association between dairy consumption and obesity. The aim of this study was to determine the effects of a dietary intervention within a multidisciplinary structured programme on reducing the consumption of SSB and SFJ and simultaneously increasing the consumption of milk and diary products in obese children/adolescents. The study included 100 participants of both sexes who had been diagnosed with obesity and participated in a five-day multidisciplinary structured programme focused on dietary intrevention. Standard anthropometric measurements and a validated questionnaire were used during the study. The mean age of the participants was 12.61±1.90 years, body mass index (BMI) was 98.38±1.26 percentiles; mean consumption of SSB was 1.68 ± 2.89 dL; SFJ was 3.72±5.09 dL and milk and dairy products was 3.10±2.35 dL per day at the start of the intervention. After the five-day programme, patients were reeducated once a month for the first six months, then every two months for up to 24 months. After 24 months, a significant decrease in SSB and SFJ intake (p<0.001) and an increase in milk and dairy products intake (p=0.002) were observed. The percentiles of the BMI also decreased after 24 months (p<0.001). The dietary intervention had a positive effect on the anthropometric values and the change in the dietary habits of the participants, with a focus on the consumption of milk and dairy products.